Step
*
of Lemma
square-rless-implies
∀x,y:ℝ. ((r0 ≤ y)
⇒ (x^2 < y^2)
⇒ (x < y))
BY
{ (Auto
THEN nRAdd ⌜-(x^2)⌝ (-1)⋅
THEN (Assert (-(x^2) + y^2) = ((y + x) * (y - x)) BY
((RWO "rnexp2" 0 THENM nRNorm 0) THEN Auto))
THEN (RWO "-1" (-2) THENA Auto)
THEN (RWO "rmul-is-positive" (-2) THENA Auto)
THEN D -2
THEN Auto) }
1
1. x : ℝ
2. y : ℝ
3. r0 ≤ y
4. (y + x) < r0
5. (y - x) < r0
6. (-(x^2) + y^2) = ((y + x) * (y - x))
⊢ x < y
Latex:
Latex:
\mforall{}x,y:\mBbbR{}. ((r0 \mleq{} y) {}\mRightarrow{} (x\^{}2 < y\^{}2) {}\mRightarrow{} (x < y))
By
Latex:
(Auto
THEN nRAdd \mkleeneopen{}-(x\^{}2)\mkleeneclose{} (-1)\mcdot{}
THEN (Assert (-(x\^{}2) + y\^{}2) = ((y + x) * (y - x)) BY
((RWO "rnexp2" 0 THENM nRNorm 0) THEN Auto))
THEN (RWO "-1" (-2) THENA Auto)
THEN (RWO "rmul-is-positive" (-2) THENA Auto)
THEN D -2
THEN Auto)
Home
Index